The Use of Social Modelling to Improve Students’ Creativity in Learning English - Safrawa, Gabriel Rachel; Talib, Ahmad; Tahir, Muh. (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The objective of this research was to find out whether or not the use of social modelling improves students’ creativity in learning English. This research used a quantitative approach with a pre-experimental design with a one-group pre-questionnaire and post-questionnaire. The participants of this research were 31 eight-grade students at SMPN 18 Makassar. They were selected using random sampling techniques. The results of the pre-questionnaire and post-questionnaire, using social modelling to improve students’ creativity in learning English, are evidenced by the value of the t-test. This can be proven by a t-test value that is lower than P (0.000 < 0.05), which means that H0 of this study is rejected and HA is accepted. So, it can be concluded that the use of social modelling can improve students’ creativity in learning English in junior high school.